Evaluation of a Bedside Immunochromatographic Test for Detection of Adenovirus in Respiratory Samples, by Comparison to Virus Isolation, PCR, and Real-Time PCR - Fujimoto, Tsuguto (American Society for Microbiology, 2004)
An immunochromatography (IC) kit for human adenovirus (HAdV) was evaluated with 138 patient nasopharyngeal samples. The samples were collected at a sentinel clinic in Japan from January through June 2003. Patients were diagnosed by clinical manifestation of pharyngoconjunctival fever (n = 38) or exudative tonsillitis (n = 100). The IC kit was positive for 84% (116 of 138) of patients diagnosed at bedside. The remaining extract solution of the IC kit test was transferred into maintenance medium and tested via laboratory diagnoses. The IC kit had 95% sensitivity (116 of 122 patients) with HAdV isolation (isolation) as the standard and 91% sensitivity (116 of 128 patients) with PCR as the standard. All of the IC kit-positive samples were isolation and PCR positive. Similarly, all the isolation-positive samples were PCR positive. Twenty-two IC kit-negative samples were evaluated by real-time PCR. Six samples were IC kit negative and isolation positive and contained 3.8 × 10(7) to 2.5 × 10(9) copies of the HAdV genome/ml. Five samples that were only PCR positive contained 3.0 × 10(4) to 3.8 × 10(5) copies of the HAdV genome/ml, but one sample was real-time PCR negative. We conclude that the IC kit is a useful bedside diagnostic tool for HAdV infections because it has 95% sensitivity (compared to isolation), but a negative result does not always rule out HAdV infection.